Dampak Implementasi Kebijakan Pajak atas Ekonomi Digital terhadap Perilaku Konsumsi Generasi Z - Ike Zahrotun Nisa; Ratih Purbasari (Jurnal Akuntansi dan Pajak, 2025)
The taxation policy on the digital economy has garnered increasing attention in various countries, including Indonesia, in line with the rapid growth of digital transactions. This article examines the impact of the implementation of such tax policies on the consumption behavior of Generation Z, known as a digital-native group highly dependent on online services and digital shopping. The study identifies how the application of taxes on digital products and services, such as e-commerce, streaming, and apps, influences Generation Z’s purchasing power and consumption decisions. Using statistical data and case studies of digital tax policies from several countries, the article finds that these policies tend to make Generation Z more selective and sensitive to price changes. Furthermore, the research highlights the challenges faced by governments in balancing the objective of increasing national revenue with efforts to maintain consumer purchasing power. These findings are expected to provide valuable insights for policymakers and industry players in formulating strategies that support the growth of the digital economy without hindering the consumption of younger generations.